2008
DOI: 10.1042/bj20071354
|View full text |Cite
|
Sign up to set email alerts
|

In vivo quantitative relationship between plastid division proteins FtsZ1 and FtsZ2 and identification of ARC6 and ARC3 in a native FtsZ complex

Abstract: FtsZ1 and FtsZ2 are phylogenetically distinct homologues of the tubulin-like bacterial cell division protein FtsZ that play major roles in the initiation and progression of plastid division in plant cells. Both proteins are components of a mid-plastid ring, the Z-ring, which functions as a contractile ring on the stromal surface of the chloroplast IEM (inner envelope membrane). FtsZ1 and FtsZ2 have been shown to interact, but their in vivo biochemical properties are largely unknown. To gain insight into the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
66
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 65 publications
(171 reference statements)
11
66
1
Order By: Relevance
“…A typical preparation was Ͼ95% pure. Quantitative amino acid analysis also demonstrated that the BCA assay underestimates recombinant FtsZ1 and FtsZ2 by ϳ20%, similar to EcFtsZ (30) and consistent with our previous quantitative analyses (20).…”
Section: Production Of Recombinant Ftsz Proteins-ftsz1supporting
confidence: 72%
See 3 more Smart Citations
“…A typical preparation was Ͼ95% pure. Quantitative amino acid analysis also demonstrated that the BCA assay underestimates recombinant FtsZ1 and FtsZ2 by ϳ20%, similar to EcFtsZ (30) and consistent with our previous quantitative analyses (20).…”
Section: Production Of Recombinant Ftsz Proteins-ftsz1supporting
confidence: 72%
“…Depletion or overexpression of either protein impairs division and results in enlarged chloroplasts, which are the phenotypic equivalent of the bacterial filamentation phenotype (17)(18)(19). These findings, along with data showing that the molar ratio between Arabidopsis FtsZ1 and FtsZ2 remains constant throughout leaf development (20), suggest that their stoichiometry is important for chloroplast division activity. In vitro, FtsZ1 and FtsZ2 have been reported to exhibit GTPase activity and to undergo GTPdependent assembly into protofilaments (21)(22)(23).…”
mentioning
confidence: 49%
See 2 more Smart Citations
“…11C; Supplemental Table S4). Two nuclear-encoded forms of filamenting temperature-sensitive Z mutants (FtsZ1, Solyc07g065050 and FtsZ2, Solyc09g009430) play a major role in the initiation and progression of plastid division in plant cells (McAndrew et al, 2008). They are both present at MG and B stages, but FtsZ1 was absent at the R stage while FtsZ2 remained stable at all three stages.…”
Section: Loss Of the Plastid Division Machinerymentioning
confidence: 99%